FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS E-COMMERCE PADA APLIKASI PENJUALAN ONLINE DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTED MODEL (TAM) (Studi Kasus Pada Pengguna E-Commerce Di Jastip Erick Ende) - Nasir, Mardiana Moh.; Sayang, Sabulon; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2024)
This study aims to determine the effect of Subjective Norms, Perceived Ease, Perceived Usefulness, and Complexity on Interest in Using E-commerce-Based Accounting Information Systems. This research is a type of quantitative research. The sampling technique used random sampling, amounting to 67 respondents. The dataanalysis technique used is descriptive statistics, data quality test, classical assumption test, multiple regression analysis and hypothesis testing. The results of this study indicate that: (1) Subjective Norm Variables do not have a significant positive effect on intention to use. This is evidenced by the regression coefficient value of the subjective norm variable of 0.142 with atcount value of 1.118 <1.99897 with a significant level of 0.268 >0.05. (2) Perceived ease of variable has a significant positive effect on intention to use. This is evidenced by the regression coefficient value of the perception of ease variable of 0.324 with atcount of 2.531 > 1.99897 with a significant level of 0.014 <0.05. (3) Perceived usefulness variable has a significant positive effect on intention to use. This is evidenced by the regression coefficient value of the perceived usefulness variable of 0.262 with atcount of 2.358 > 1.99897 with a significant level of 0.022 <0.05. (4) Complexity variable has no significant positive effect on intention to use. This is evidenced by the regression coefficient value of the complexity variable of 0.122 with atcount value of 0.919 <1.99897 with a significant level of 0.362 >0.05. Based on the results of the test for the coefficient of determination (R2) it shows that the percentage of the influence of the independent variables (subjective norms, perceived convenience, perceived usefulness and complexity) on the dependent variable (intention to use) is 39.8% while the remaining 60.2% is influenced by other variables that not included in this study.